Can job autonomy attenuate the effect of depression on employees' well-being? It may depend on culture. (4th March 2019) - Li, Liman Man Wai
Abstract: Background : Depression is one of the leading causes of work disability. Thus, it is important to explore possible ways to reduce its impact on employees. Aims : The current research examined whether promoting job autonomy would attenuate the detrimental effect of depression on employees' well-being. Methods : Study 1 included the data from 5974 full-time employees from China. Full-time employees living in India, a collectivistic culture, and the United States, an individualistic culture, were recruited online in Study 2. Results : Study 1 revealed that job autonomy moderated the influence of depression on job strain and perceived control mediated this interaction effect. Specifically, job autonomy weakened the detrimental effect of depression on job strain via weakening the association between depression and perceived control. The data from the 258 full-time employees in Study 2 replicated the findings and found that job autonomy had a stronger attenuating effect on the influence of depression in India than it had in the United States. Conclusions : Job autonomy was found to be an effective way to reduce the negative impact of depression on employees' well-being, a finding that should be considered when organizations develop their work policies.